2019
DOI: 10.1186/s12903-019-0795-4
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries experience, care index and restorative index in children with learning disabilities and children without learning disabilities; a systematic review and meta-analysis

Abstract: Background Children with learning disabilities (CLD) have worse health outcomes than children with no learning disabilities (CNLD). This systematic review compared caries experience and met dental care need for CLD to CNLD using Decayed, Missing, Filled Permanent Teeth (DMFT) and decayed, missing/extracted, filled primary teeth (dmft/deft), care index (CI), and restorative index (RI) values. Methods Without date or language restrictions four databases were searched for;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 60 publications
(212 reference statements)
3
24
0
4
Order By: Relevance
“…Of the 24 included reviews, 6 were on sleep; 10-15 3 on sensory impairments (not sensory sensitivities; 1 on peripheral hearing loss, 18 1 on visual impairment, 19 and 1 on visual or hearing impairment 20 ); 3 on epilepsy; 7-9 3 on oral health; 21-23 1 on asthma 26 and 1 on allergic asthma; 27 1 each on diabetes, 16 gastro-intestinal conditions, 17 atopic dermatitis, 24 autoimmune disease, 25 obesity, 28 incontinence; 29 and 1 review on 5 conditionsimmunological, gastrointestinal, incontinence, epilepsy and hypospadias. 30 Fifteen studies were on children and young people, 11,13,14,[16][17][18][19][20][21][22][23][24][25][26][27] 8 were on children, young people and adults, [7][8][9]12,15,[28][29][30] and 1 study was on adults only. 10 Although the quality of the included reviews was good, most, in their own quality assessments, reported several limitations in the papers they included, and also considerable heterogeneity that precluded meta-analysis for several of the reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 24 included reviews, 6 were on sleep; 10-15 3 on sensory impairments (not sensory sensitivities; 1 on peripheral hearing loss, 18 1 on visual impairment, 19 and 1 on visual or hearing impairment 20 ); 3 on epilepsy; 7-9 3 on oral health; 21-23 1 on asthma 26 and 1 on allergic asthma; 27 1 each on diabetes, 16 gastro-intestinal conditions, 17 atopic dermatitis, 24 autoimmune disease, 25 obesity, 28 incontinence; 29 and 1 review on 5 conditionsimmunological, gastrointestinal, incontinence, epilepsy and hypospadias. 30 Fifteen studies were on children and young people, 11,13,14,[16][17][18][19][20][21][22][23][24][25][26][27] 8 were on children, young people and adults, [7][8][9]12,15,[28][29][30] and 1 study was on adults only. 10 Although the quality of the included reviews was good, most, in their own quality assessments, reported several limitations in the papers they included, and also considerable heterogeneity that precluded meta-analysis for several of the reviews.…”
Section: Resultsmentioning
confidence: 99%
“…21 Dental caries are common, but results are inconsistent as to whether they are more common than in the general population, and on comparisons of dental treatment for caries. [21][22][23] (d) Findings on peripheral hearing loss are inconsistent. 18 Among people with hearing impairment, the relative risk of ASD was high.…”
Section: How Common Are Comorbid Physical Conditions In People With Asd?mentioning
confidence: 99%
“…Children with ASD have poor oral health and they present high care demands, which requires much time, effort, and patience [ 8 , 51 ]. Findings of this study suggest the feasibility of the MyDentist approach and the positive role of technology support [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASD varies greatly in the severity of associated socio-communicative impairments and in the degree of cognitive and language development [ 4 ]. Although there is no specific relationship between ASD and oral disease, it is well-recognized that many individuals with ASD have much worse oral health than non-autistic people [ 5 , 6 , 7 , 8 , 9 , 10 ]. This may be related to barriers to dental services, sensory sensitivities and heightened levels of stress and anxiety during care; these factors may affect the level of cooperation of individuals with ASD in regard to daily hygiene routines, oral exams, and dental care [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Öğrenme güçlüğü olan çocukların diş çürüğü, ağız bakımı ve restorasyonlarının incelendiği bir sistematik derlemenin sonucunda; öğrenme güçlüğü olan ve olmayan çocukların süt dişlerinde ve daimi dişlerinde diş çürüğü karşılaştırması açısından kesin bir kanıt olmadığı belirlenmiştir. Öğrenme güçlüğü olan çocukların alt gruplarında, Down sendromu hariç diğer çocukların diş çürüğü seviyesi açısından benzerlik gösterdiği, Down sendromlu çocukların daimi dişlerinde diş çürüğünün daha az olduğu belirtilmiştir (14). Down sendromlu bireylerde diş çürüğünün daha düşük görülmesinin nedenleri arasında; dişlerin diastemalı olması, dişlerin geç sürmesi, tükürük kimyasının farklı olması, hipodonti, oligodonti, mikrodonti görülmesi ve bruksizme bağlı olarak diş yüzeylerinin düzleşmesi yer almaktadır (15) (11,17).…”
Section: Introductionunclassified